The Determinants of Financial Performance of State-Owned Banks in Indonesia - M. Puspitasari, Devy; Haizam Mohd Saudi, Mohd; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study is to investigate the determinants of financial performance of state-owned banks in Indonesia. Design/methodology/approach: The method used in this study uses panel data. The data used are secondary data obtained from bank publication reports for the period 2007-2017. The population used in this study is a state-owned bank, and sample selection is based on purposive sampling. Findings: The results showed that the leverage measured by the DER ratio had a negative and significant effect on the financial performance (ROA) of state-owned banks in Indonesia. The effect of loan deposit ratio, debt equity ratio, and capital adequacy ratio together is still low on the financial performance of state-owned banks in Indonesia. Loan deposit ratio that does not have a real effect on financial performance; it is better if the loan distribution is adjusted to the economic conditions faced. An aggressive credit distribution strategy is not always profitable for banks, especially when in uncertain economic conditions.